Примените распределительный закон умножения (x+6)*30 (10-a)*5 4*(7+y) 11*(m-2)

Примените распределительный закон умножения (x+6)*30 (10-a)*5 4*(7+y) 11*(m-2)
Гость
Ответ(ы) на вопрос:
Гость
(х+6)*30=х*30+6*30=30х+180                                                                              (10-а)*5=10*5-а*5=50-5а                                                                                       4*(7+у)=4*7+4*у=28+4у                                                                                        11*(m-2)=11*m-11*2=11m-22             
Не нашли ответ?
Ответить на вопрос
Похожие вопросы